The More the Gloomier: development of informal employment and its effect on wages in Turkey - Anil Duman; Alper Duman (Global Labor Organization (GLO), 2021)
Various studies found wage gaps between formal and informal sector workers even after controlling for a number of individual and firm level characteristics. It has also been shown that earnings differentials across these sectors are quite stable over the years. While there is limited amount of research considering the same issues focusing on Turkish labor market, the development of wage gap between formal and informal employment has not been examined. In our paper, we carry this analysis for Turkey and estimate the wage gap between formal and informal sector workers by utilizing the Household Labor Force Survey (LFS) for the period of 2005 and 2019. There are three main findings; first, decline in informal employment is not uniform and especially after 2012 there is a slight increase in the share of informal jobs at the lower end of wage distribution. Second, we demonstrate that returns to informality vary significantly across quantiles even after a matching technique through inverse probability treatment weights are considered. While at the upper end of the distribution, the penalty is extremely small and stable over the years, at the bottom end, the informal sector considerably reduces wages, and the effect becomes larger over time. The negative and increasing penalty is observable well before the refugee inflows. The last part of our analysis looks at the occupational composition within formal and informal sectors over time and points out that the rise of white collar low skilled service (WCLS) jobs among informal employment is mainly responsible for the increasing wage gap for the workers at the bottom end.
Keywords: J31; C31; O17; J46; 330; wage gap; quantile regression; informal sector; compensation; skills; occupation